Theoretical Model for Determination of Airspace Capacity - Lučovnik, Brane; Lipičnik, Martin; Lebar, Domenik; Blatnik, Janko (Promet - Traffic&Transportation, 2002)
In the last decade, the constant air traffic growth hasbrought certain problems as well. While aircraft productionand airline functioning are being stimulated by the competition,the situation in air traffic control and in infrastructurecomponent is completely different. Air traffic management(ATM) is still owned by the state. The state, however, is knownfor the fact of not being a good manager and is solving problemsslowly and not efficiently because of its large administration.There is a very strong trade union movement functioningin ATM, which makes several rational decisions impossible.Critics of the current ATM system in Europe warn of increasingproblems -delays and operational expenses. The control componentis the only one among the four components of air traffic,which has not been liberalised and harmonised yet. There is nocompetition in the fields of air traffic. All matters are taken careof by CAA or by semi-private companies, owned by the state.According to air carriers which have to put in 4-9% of businessexpenses into terminal- and over-flight charges, these expensesare far too heavy a burden.